Genetics of Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome: advancements and implications - Herlin, Morten Krogh (Frontiers in Endocrinology, 2024)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is a congenital anomaly characterized by agenesis/aplasia of the uterus and upper part of the vagina in females with normal external genitalia and a normal female karyotype (46,XX). Patients typically present during adolescence with complaints of primary amenorrhea where the diagnosis is established with significant implications including absolute infertility.Most often cases appear isolated with no family history of MRKH syndrome or related anomalies. However, cumulative reports of familial recurrence suggest genetic factors to be involved. Early candidate gene studies had limited success in their search for genetic causes of MRKH syndrome. More recently, genomic investigations using chromosomal microarray and genome-wide sequencing have been successful in detecting promising genetic variants associated with MRKH syndrome, including 17q12 (LHX1, HNF1B) and 16p11.2 (TBX6) deletions and sequence variations in GREB1L and PAX8, pointing towards a heterogeneous etiology with various genes involved. With uterus transplantation as an emerging fertility treatment in MRKH syndrome and increasing evidence for genetic etiologies, the need for genetic counseling concerning the recurrence risk in offspring will likely increase.This review presents the advancements in MRKH syndrome genetics from early familial occurrences and candidate gene searches to current genomic studies. Moreover, the review provides suggestions for future genetic investigations and discusses potential implications for clinical practice.